2023
DOI: 10.1101/2023.01.30.526262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CD39+conventional CD4+T cells with exhaustion traits and cytotoxic potential infiltrate tumors and expand upon CTLA-4 blockade

Abstract: Background: Conventional CD4+ T (Tconv) lymphocytes play important roles in tumor immunity; however, their contribution to tumor elimination remains poorly understood. Methods: Here we describe a subset of Tconv cells characterized by the expression of CD39. The phenotype, the effector function and transcriptional profile of tumor-infiltrating CD39+ Tconv lymphocytes from different mouse cancer models and breast cancer patients were studied by multiparametric flow cytometry and RNA sequencing. The impact of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…However, we detected high frequencies of PD-1 + , CD39 + , CD107a + , and GZMB + CD4 + Tconv cells, particularly in patients during the first wave, suggesting that these T cells were activated and prone to be exhausted. In agreement with this, but in a different setting characterized by significant inflammation, it has been found that CD39 + CD4 + tumorinfiltrating Tconv cells from patients with breast cancer display features of exhaustion while retaining the ability to produce effector cytokines (56). In agreement with our observation, cytotoxic CD4 + T cells producing GZMB, perforins, and CD107a, have been widely described in respiratory viral infections (43,57) production in severely diseased patients is associated with persistent expansion of hyperactivated effector CD4 + and CD8 + T cells capable of secreting GZMB.…”
Section: Discussionsupporting
confidence: 61%
“…However, we detected high frequencies of PD-1 + , CD39 + , CD107a + , and GZMB + CD4 + Tconv cells, particularly in patients during the first wave, suggesting that these T cells were activated and prone to be exhausted. In agreement with this, but in a different setting characterized by significant inflammation, it has been found that CD39 + CD4 + tumorinfiltrating Tconv cells from patients with breast cancer display features of exhaustion while retaining the ability to produce effector cytokines (56). In agreement with our observation, cytotoxic CD4 + T cells producing GZMB, perforins, and CD107a, have been widely described in respiratory viral infections (43,57) production in severely diseased patients is associated with persistent expansion of hyperactivated effector CD4 + and CD8 + T cells capable of secreting GZMB.…”
Section: Discussionsupporting
confidence: 61%